Tinjauan Hukum Islam Terhadap Praktik Gadai Tanah Terdapat Bangunan Yang Ditempati (Studi Kasus Desa Margawiwitan 2, Kecamatan Sumber Jaya, Kabupaten Lampung Barat) - Dimas Wijaya; Muhammad Zaki; Agus Hermanto (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The practice of pawning land containing buildings still occupied by tenants in Margawiwitan 2 Village, Sumber Jaya District, West Lampung Regency, raises Islamic legal issues related to the protection of the rights of the parties in the rahn contract. The problem of this research is how the practice of pawning land containing occupied buildings takes place and how Islamic law views this practice. This study aims to determine the mechanism of pawning implementation that occurs in the community and analyze its compliance with Islamic law provisions. The research method used is qualitative research with a descriptive analysis approach. Primary data were obtained through interviews with land and building owners (rahin), building tenants, and pawn recipients (murtahin), while secondary data were obtained from the Qur'an, hadith,books on muamalah fiqh, books, scientific journals, and previous research. The results of the study indicate that the practice of pawning is carried out due to economic needs by pawning land and buildings that have been previously leased without any transparency of information to the tenant or pawn recipient. This practice contains elements of gharar due to the unclear status of the pawned object and the clause of automatic transfer of ownership to the murtahin if the debt is not repaid. Based on Islamic law, this practice does not fully comply with the principle of rahn because it ignores the rights of the lessee, ignores the principle of transparency, and contradicts the provision that pawned goods do not immediately become the property of the pawned person but must first be sold to repay the debt. Therefore, it is necessary to implement a contract that upholds the principles of justice, transparency, and protects the rights of all parties involved, in accordance with Islamic law.